2010
DOI: 10.1177/1352458510369147
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin treatment in patients with relapsing-remitting multiple sclerosis receiving interferon beta 1a: a double-blind randomized controlled trial

Abstract: ClinicalTrials.gov NCT00668343. This interventional study provides Class I evidence stating that adding simvastatin 40 mg/day to IFNb 1a 30 microg a week in patients with relapsing-remitting multiple sclerosis may reduce the relapse rate (moderate effect size r = 0.29) (p = 0.01) compared with treatment with IFNb 1a alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 23 publications
1
38
1
1
Order By: Relevance
“…Exacerbations were verified by an evaluating MS physician or trained registered nurse using the same definition implemented in recent DMT trials. 16 Participants were also evaluated clinically at 16-week intervals to document their EDSS and adverse events. Patients with confirmed exacerbations were referred to their physicians for treatment.…”
Section: Assessment Masking All Clinical Evaluators and Techniciansmentioning
confidence: 99%
See 1 more Smart Citation
“…Exacerbations were verified by an evaluating MS physician or trained registered nurse using the same definition implemented in recent DMT trials. 16 Participants were also evaluated clinically at 16-week intervals to document their EDSS and adverse events. Patients with confirmed exacerbations were referred to their physicians for treatment.…”
Section: Assessment Masking All Clinical Evaluators and Techniciansmentioning
confidence: 99%
“…The lost to follow-up rate of 22% in SMT-MS is comparable to many other trials of behavioral interventions, 29 while the loss of 10% of participants in the wait list control condition is consistent with rates seen in pharmaceutical trials in MS trials more generally. 16,30 There was no evidence that dropout was related to demographic or diseaserelated variables and our statistical analyses attempted to control for the lost to follow-up using imputation. However, it is possible that there were other unmeasured variables that that could have introduced bias.…”
mentioning
confidence: 99%
“…4,5 Two meta-analyses of statins (atorvastatin and simvastatin) that examined the same trials found that there is no benefit of statins in regard to MS relapse rates, disease progression, or change in disability scores.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that the addition of simvastatin 40 mg daily to interferon therapy may reduce the relapse rate (moderate effect size, r = 0.29). 4 In a double-blind, placebo-controlled multicenter trial, 307 treatment-naïve patients with relapsingremitting MS received intramuscular interferon beta-1a (30 mcg weekly) for 3 months prior to randomization to concurrent therapy with simvastatin or placebo for at least 12 months and up to 36 months. Simvastatin was dosed as 40 mg daily for one month then increased to 80 mg daily.…”
Section: Controlled Trialsmentioning
confidence: 99%
“…In an MRIbased study in patients with RR-MS, treatment with atorva statin, alone or in combination with IFN-β, led to a substantial reduction in the number and volume of CEL [139]. Moreover, a clinical study in RR-MS suggested that adding statins to IFN-β may reduce the relapse rate compared with IFN-β alone [140]. However, it has been shown that statins impair remyelination in vitro and in vivo [141].…”
Section: Promising Therapeutic Concepts With Putative Neuroprotectivementioning
confidence: 99%